2020
DOI: 10.3329/jss.v23i1.44241
|View full text |Cite
|
Sign up to set email alerts
|

Management and Outcome of Diabetic Foot-A Study of Hundred Case

Abstract: Background: Diabetes mellitus is a complex metabolic disorder that affect 1-2 percent of the population. It can give rise to many tissue complications among which foot is particularly vulnerable to circulatory and neurological disorder, so that even minor trauma can lead to ulceration and infection. Methods: Between September 2008 and August 2009, 100 patients were undergone treatment for diabetic foot at department of Surgery, Shaheed Ziaur Rahman Medical College Hospital, Bogra. This study included all… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 4 publications
0
1
0
Order By: Relevance
“…Additionally, pressure applied to the region reaches out without the patient being taken note of. Wound size likewise assumes a key job in visualization, and this examination found that individuals with UPD> 5 cm in distance across had more regrettable results than those with littler ulcers [21][22]. These discoveries are like the discoveries of another US study that found that risk factors or wound qualities most drastically connected with wound recuperating disappointment expanded the size and length of wound healing [23].…”
Section: Resultsmentioning
confidence: 69%
“…Additionally, pressure applied to the region reaches out without the patient being taken note of. Wound size likewise assumes a key job in visualization, and this examination found that individuals with UPD> 5 cm in distance across had more regrettable results than those with littler ulcers [21][22]. These discoveries are like the discoveries of another US study that found that risk factors or wound qualities most drastically connected with wound recuperating disappointment expanded the size and length of wound healing [23].…”
Section: Resultsmentioning
confidence: 69%